Effect of cadmium on essential metals and their impact on lipid metabolism in Saccharomyces cerevisiae - Rajakumar, Selvaraj (Cell Stress Chaperones, 2019)
Cadmium (Cd) is a toxic heavy metal that induces irregularity in numerous lipid metabolic pathways. Saccharomyces cerevisiae, a model to study lipid metabolism, has been used to establish the molecular basis of cellular responses to Cd toxicity in relation to essential minerals and lipid homeostasis. Multiple pathways sense these environmental stresses and trigger the mineral imbalances specifically calcium (Ca) and zinc (Zn). This review is aimed to elucidate the role of Cd toxicity in yeast, in three different perspectives: (1) elucidate stress response and its adaptation to Cd, (2) understand the physiological role of a macromolecule such as lipids, and (3) study the stress rescue mechanism. Here, we explored the impact of Cd interference on the essential minerals such as Zn and Ca and their influence on endoplasmic reticulum stress and lipid metabolism. Cd toxicity contributes to lipid droplet synthesis by activating OLE1 that is essential to alleviate lipotoxicity. In this review, we expanded our current findings about the effect of Cd on lipid metabolism of budding yeast.